Loss of Eyebrows and Eyelashes During Concomitant Treatment with Sitagliptin and Metformin - Succurro, Elena; Palleria, Caterina; Ruffo, Mariafrancesca; Serra, Raffaele; Arturi, Franco; Gallelli, Luca (Current Drug Safety, 2017)
The fixed dose combination of sitagliptin 50 mg and metformin 850 mg (Janumet ®), is indicated for the treatment of type 2 diabetes mellitus in addition to diet and exercise to improve glycemic control in patients treated with metformin alone. Methods: We report a 69-year-old man with type 2 diabetes that developed sudden loss of eyebrows and eyelashes about 4 months after the beginning of Janumet®. Clinical and laboratory findings excluded the presence of systemic or skin diseases able to induce these manifestations, while the Naranjo probability scale documented a possible association between the drug and the adverse drug reaction.
Keywords: Adverse drug reaction